Millenium Gypsum Board / Noor Yushalizawati Md Yunus ... [et al.] - Md Yunus, Noor Yushalizawati; Abd Halim, Shaiful Azhar; Omar, Zuraini; Ghazli, Sumaiyah; Jafar, Khamal Rul Fairul
The purpose of having business plan for our business "Millennium Gypsum Board" is to provide us a resource that can be used as a reference and guideline for operating our business activities. With this we can analyze and evaluate our business potential. Besides that, we can look whether the business has a wide range of business opportunities and whether this particular business has the potential to expand in the bear future. By having this business plan, we can arrange strategies and estimate our future problems and business activities for the first years, to see if we can compete in the business environment. Secondly, the purpose of the business plan is to provide a reference to the external parties such as lenders, suppliers, and inventors. This business plan is to show to our supplies and the lenders that we have the opportunity to expend our business in the future and we have the ability to pay back any loan that we have been made. Last but not least, the business plan will act as a guidelines for us to start the business and run it in order to become among those Bumiputra's who are already involve in the business world.